THE USE OF SOCIAL MEDIA FOR LEARNING ENGLISH: STUDENTS PERSPECTIVE - Muetia Safitri; Atik Yuliyani; Farida Hamid; Aminah Suriaman (University of Kuningan, 2022)
Social media has become the most influence media used by people. It changes the way people communicate and access information. Although it is not directly created for educational purposes, it has drawn educators' attention, especially in the English language learning field. Several studies have concluded that social media can be used as media in English classroom. However, to use social media effectively, it’s important to know student’s perception as reference for teacher in using social media. Thus the present study was conducted to explore high-school students’ perception of social media use for English learning. 83 students of one private Senior High School in Depok, Indonesia, were involved in this study. The study employed a qualitative approach with a case study design using questionnaires and semi-structured interview as data collection methods. Basic statistical analysis was used to analyze data from the questionnaire, and the data from interviews were analyzed using the flow model by Miles and Huberman. The results showed that the students in this study use social media for improving their English. They choose YouTube as the most used social media for learning English. Further, they stated that social media provides English content sources to practice their English skills, enlarges their vocabulary and pronunciation knowledge. They also stated the challenges in using social media for learning, such as internet connection problems, privacy, and inappropriate content.Keywords: English learning; social media; students’ perception